Geophysics - Investigating the innacessible - Ernesto, Marcia; Caminha-Maciel, George (Cadernos de Astronomia, 2022)
This work presents some aspects of Geophysics dealing with physical manifestations that bring information about the Earth’s internal structure. In this way, some basic concepts about seismology, the study of elastic waves released by earthquakes, geomagnetism, the study of the magnetic field generated inside the Earth, and gravimetry, the interpretation of gravimetric anomalies produced by heterogeneities in the Earth's internal structures are addressed.
Keywords: geophysics; seismology; geomagnetism; gravimetry